TRANSLATION THEORY AND PRACTICE - Egamberdiyev Jasurbek; Xakimova Gulxumor; Bozorboyeva Roziya (Journal of new century innovations, 2023)
Annotation: This scientific article explores the relationship between translation theory and practice, highlighting the importance of integrating theoretical frameworks with practical considerations for achieving effective cross-language communication. Drawing on interdisciplinary perspectives from translation studies, linguistics, and communication studies, the article examines key concepts, methodologies, and challenges in translation theory and practice. By examining the dynamic interplay between theory and practice, this article aims to enhance our understanding of translation as a complex and multifaceted process and provide insights into improving translation outcomes in various contexts.